Artificial cellular nano-environment composed of collagen-based nanofilm promotes osteogenic differentiation of mesenchymal stem cells. (1st March 2019) - Hwang, Jun-Ha; Han, Uiyoung; Yang, Miso; Choi, Yonghyun; Choi, Jonghoon; Lee, Jong-Min; Jung, Han-Sung; Hong, Jinkee; Hong, Jeong-Ho
Graphical abstract: Abstract: In regenerative medicine, the generation of therapeutic stem cells and tissue engineering are important for replacing damaged tissues. Numerous studies have attempted to produce cellular components that mimic the native tissue for gaining optimal function. Particularly, the extracellular matrix (ECM) composition plays an important role in cellular functions including determining the fates of mesenchymal stem cells (MSCs). Here, we evaluated the osteogenic effects of a nanofilm in which oppositely charged polyelectrolytes were alternately adsorbed onto the cell surface to create an artificial ECM environment for single MSCs. Interestingly, nanofilm composed of collagen (Col) and alginate (AA) showed relatively high stiffness and MSCs coated with the Col/AA nanofilm showed increased osteogenic differentiation efficiency compared to other nanofilm-coated MSCs. Further analysis revealed that the Col/AA nanofilm coating stimulated osteogenesis by activating transcriptional coactivators with the PDZ binding motif through extracellular signal-related kinase and p38 MAPK signaling. This nano-sized cellular coating will facilitate the development of nanotechnology for controlling cellular functions and advance stem cell-based clinical applications for regenerative medicine. State of Significance: In this study, we developed an artificial cellular nano-environment formed by multilayer nanofilms. We demonstrated that the nanofilms introduced to mesenchymal stem cells (MSCs) stimulate osteogenic differentiation by regulating intracellular signaling. Among the various nanofilm combinations, the induction of osteogenic gene transcription in collagen (Col) and alginate (AA) film-coated MSCs was the most pronounced compared to that on other nanofilms. A minimum number of Col/AA nanofilm bilayers (n = 2) was required for effective induction of MSC osteogenic differentiation. In addition, we observed the correlation between the promoting effect of osteogenic differentiation and stiffness of the nanofilm. Our results may be useful for developing a cell coating model system widely applicable in bioengineering and regenerative medicine.